2021
DOI: 10.1039/d1ra03937g
|View full text |Cite
|
Sign up to set email alerts
|

In silico study of natural compounds from sesame against COVID-19 by targeting Mpro, PLpro and RdRp

Abstract: Natural products and traditional medicine products with known safety profiles are a promising source for the discovery of new drug leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…Other studies also indicated that the sesamin compound might interact with amino acid residues Ser144, Cys145, Gln189, and Gln192 and showed significant interactions with effective residues His41, Met49, and Met165 of the M pro of COVID-19 (Pandey and Verma, 2020). In a follow-up study, Allam et al (2021) explored the sesamin and sesamolin compounds along with other natural compounds against M pro , PL pro , and RdRp proteins. Sesamin was found to be interacted with M pro with three residues including Gln189, Thr190, and His41, while the sesamolin molecule was reported to interact with two amino acid residues, namely, Gln189 and Thr190.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also indicated that the sesamin compound might interact with amino acid residues Ser144, Cys145, Gln189, and Gln192 and showed significant interactions with effective residues His41, Met49, and Met165 of the M pro of COVID-19 (Pandey and Verma, 2020). In a follow-up study, Allam et al (2021) explored the sesamin and sesamolin compounds along with other natural compounds against M pro , PL pro , and RdRp proteins. Sesamin was found to be interacted with M pro with three residues including Gln189, Thr190, and His41, while the sesamolin molecule was reported to interact with two amino acid residues, namely, Gln189 and Thr190.…”
Section: Compoundmentioning
confidence: 99%
“…In a recent study, Pandey and Verma (2020) also studied the potential of sesamin and four other dietary components (galangin, ellagic acid, capsaicin, and epicatechin) as structural inhibitors of SARS-CoV-2 M pro using the molecular docking approach. In a very recent study, Allam et al (2021) reported seven sesame-derived natural compounds (sesamin, sesamolin, pinoresinol, hydroxymatairesinol, spicatolignan, ferulic acid, and vanillic acid) as potential inhibitors against three proteins of SARS-CoV-2 including M pro , papain-like protease (PL pro ), and the RNA-dependent RNA polymerase (RdRp) using the molecular docking analysis followed by MD simulations on 50 ns for representative complexes. However, there is no significant evidence of docking results evaluation available for MD simulations on high nanosecond scale (up to 200 ns) to understand the inhibitory mechanism of all sesame-derived compounds against the SARS-CoV-2 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The production part was carried out for 100 ns with the time step of 2 fs. Pymol and VMD 1.9.1 ( 36 ) were used to visualize the trajectory. Lastly, data analyses were performed for each complex and free PLpro by using root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), the radius of gyration (Rg), and solvent-accessible surface area (SASA).…”
Section: Docking Methodologymentioning
confidence: 99%
“…RdRp has proven to be a good antiviral target for coronaviruses, and several intriguing compounds have antiviral effects by targeting RdRp-for example, theaflavin [33]. Moreover, sesamin, sesamolin, pinoresinol, hydroxymatairesinol, spicatolignan, ferulic acid, and vanillic acid were tested in silico against three major proteins of SARS-CoV-2, including, 3CLpro, PLpro and RdRp [195]. Moreover, a virus replication enzyme, helicase or Nsp13, is involved in the unwinding of viral RNA.…”
Section: The Therapeutic Targets Against Coronavirusmentioning
confidence: 99%